1988
DOI: 10.1002/pssa.2211080212
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and grain boundary internal friction peaks in AlMgSi

Abstract: Polycrystalline specimens of Al–1% Mg2Si (0.2% excess Si), annealed at temperatures between 443 and 650 K after solution treatment and water quench show an internal friction peak at 480 K (1 Hz). It is proposed as a Si precipitate grain boundary peak. In macrocrystals, another peak appears during the first cooling from 620 K. It is located at 465 K (1 Hz), but under long aging it shifts to higher temperatures and increases its height. From this and other characteristics, it is concluded that this peak originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In a previous work [3], it is found that the effect is also observable in large grained specimens (macrocrystals), but there are definite differences in characteristics and behaviour between this peak and that detected in polycrystalline samples. These facts lead to the conclusion that they are two different effects arising from also different relaxation mechanisms.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…In a previous work [3], it is found that the effect is also observable in large grained specimens (macrocrystals), but there are definite differences in characteristics and behaviour between this peak and that detected in polycrystalline samples. These facts lead to the conclusion that they are two different effects arising from also different relaxation mechanisms.…”
Section: Introductionmentioning
confidence: 69%
“…The internal friction experimental curves were analyzed assuming an internal friction background obeying an exponential law and symmetric Debye peaks characterized by height, width, and temperature position as in [3].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations